Exploring Phenotypic Characteristics of Edible Caterpillars and Indigenous Knowledge of Host Plants in the Coastal Forest Ecosystems for Improved Food Security - Katana, John Juma; Mosi, Reuben Oyoo; Oyieke, Helida (East African Journal of Agriculture and Biotechnology, 2024)
Edible caterpillars have nutritional and economic value, thus providing food security at the household level during their harvesting seasons. Despite the significant value of these insects, they are harvested seasonally, and there is little or no documented research about the edible caterpillar species and their phenotypic characteristics, their host plants, and the effects of ecosystem utilization on the insects. This study explored the phenotypic characteristics of edible caterpillars and the indigenous knowledge of their host plants in selected coastal forest ecosystems, aiming to contribute to the improvement of food security. The study adopted a cross-sectional observational study design, involving data collection on caterpillar phenotypic characteristics and interviewing local communities on host plant preferences. One-way ANOVA was used to test for significant differences in phenotypic characteristics (body weight, body length, and body girth) among the four caterpillar species. The Chi-Square test was used to examine the association between caterpillar species and their preferred host plants. The findings show that the region is dominated by four edible species of caterpillars: Bunea alcinoe, Gonimbrasia zambezina, Gynanisa maja, and Menipe spp. These caterpillar species have distinct and discernible differences in their phenotypic characteristics, specifically in terms of body weight, body length, body girth, body color, as well as body texture with a significance level of 0.000. These variations in physical traits suggest that each species has evolved unique adaptations to their respective environments and may have different ecological roles within their habitats. These species also have varying preferences for different host plants, making each species unique. The preferred host plant species supporting the caterpillars were: Balanites wilsoniana for B. alcinoe, Mangifera indica for G. zambezina, Acacia gourmaensis for G. maja, and Ochna mossambicensis for Menipe spp. The study revealed significant associations between caterpillar species and their preferred host plants, indicating that the local community possesses specific indigenous knowledge regarding the preferred host plants for edible caterpillars in the study area
Keywords: Edible caterpillars; Host plants; Species; Indigenous knowledge